Biomechanical analysis of ramp ambulation of transtibial amputees with an adaptive ankle foot system - Fradet, Laetitia; Alimusaj, Merkur; Braatz, Frank; Wolf, Sebastian Immanuel (Gait & posture, 2010)
The fixed neutral position of conventional prosthetic feet causes difficulties for transtibial amputees (TTAs) when walking on ramps. New microprocessor-controlled prosthetic ankles such as the Proprio-Foot® (Össur) aim to reduce these difficulties by modifying the prosthetic ankle angle according to the gait condition. The purpose of the present investigation was to assess the biomechanical effects of adaptation of the prosthetic ankle on ramp ambulation in TTAs. Sixteen TTAs and 16 controls underwent a conventional 3D gait analysis while walking up and down a ramp. TTAs walked with the prosthetic foot set to a neutral mode angle and set to the adapted mode. Norm distance, sagittal kinematics and kinetics were calculated for comparisons between TTAs and controls. During ramp ascent, the dorsiflexion brought about by the adapted prosthetic ankle reduced the increased knee extension noted on the TTAs’ involved side and the increased plantarflexion on their sound side. During ramp descent, the plantarflexion of the adapted mode increased the adaptation mechanisms observed in TTAs. These findings suggest that the adapted mode leads to more physiologic kinematics and kinetics in the lower limbs in TTAs during ramp ascent but not during ramp descent. However, in the adapted mode, patients reported feeling safer during ramp descent, thus indicating that there might be other safety related measures such as toe-clearance or coefficient of friction influencing this perception.
Gesehen am 17.10.2023